Evaluating the governance and preparedness of the Lebanese health system for the COVID-19 pandemic: a qualitative study - Rasha Hamra; Marianne Moussallem; Anna Zein-El-Din; Alissar Rady; Michèle Kosremelli Asmar; Ibrahim R Bou-Orm (BMJ Open)
Objectives This study aimed to assess the capacities and governance of Lebanon’s health system throughout the response to the COVID-19 pandemic until August 2020.Design A qualitative study based on semi-structured interviews.Setting Lebanon, February–August 2020.Participants Selected participants were directly or indirectly involved in the national or organisational response to the COVID-19 pandemic in Lebanon.Results A total of 41 participants were included in the study. ‘Hardware’ capacities of the system were found to be responsive yet deeply influenced by the challenging national context. The health workforce showed high levels of resilience, despite the shortage of medical staff and gaps in training at the early stages of the pandemic. The system infrastructure, medical supplies and testing capacities were sufficient, but the reluctance of the private sector in care provision and gaps in reimbursement of COVID-19 care by many health funding schemes were the main concerns. Moreover, the public health surveillance system was overwhelmed a few months after the start of the pandemic. As for the system ‘software’, there were attempts for a participatory governance mechanism, but the actual decision-making process was challenging with limited cooperation and strategic vision, resulting in decreased trust and increased confusion among communities. Moreover, the power imbalance between health actors and other stakeholders affected decision-making dynamics and the uptake of scientific evidence in policy-making.Conclusions Interventions adopting a centralised and reactive approach were prominent in Lebanon’s response to the COVID-19 pandemic. Better public governance and different reforms are needed to strengthen the health system preparedness and capacities to face future health security threats.